Crizotinib resistance overcome by ceritinib in an ALK-positive non-small cell lung cancer patient with brain metastases: A case report. Issue 45 (November 2017) - Zhu, Zhouyu; Chai, Ying
Abstract: Rationale: The treatment of non-small cell lung cancer (NSCLC) has now changed dramatically in recent years and anaplastic lymphoma receptor tyrosine kinase (ALK) inhibitors are developing rapidly. Patient concerns: Here we reported a 57-year-old ALK-positive NSCLC man with brain metastases. Diagnoses: A case of lung adenocarcinoma with brain metastases. Interventions: Crizotinib was administered orally at a dose of 250mg twice a day until the brain metastases were found. Treatment with orally administered ceritinib at a dose of 450mg/d was initiated after crizotinib treatment. Outcomes: The patient is currently receiving maintenance ceritinib treatment, with no evidence of extracranial or intracranial tumor progression for 25 months. Lessons: Ceritinib may be a good choice for ALK-positive NSCLC patients with brain metastases who acquire resistance to crizotinib.